(untitled) (Journal of actual problems of jurisprudence, 2018)
Features of legal migrant workers work regulation are caused, first of all, by opportunities of General Work Society creation in our country based on the developed market economy, and also, in general, with change of legal and political system of the Kazakhstan society. Especially sharply there is a matter in connection with strengthening of integration processes within modern world politics and emergence of large economic blocks which participant of the Republic of Kazakhstan becomes. In particular, since January 1, 2015 the contract of the Eurasian Economic Union (EEU) creation directed to strengthening socially – economic processes between member countries has come into force: to formation of uniform commodity market, services, the capital and that is especially important, a manpower. In this context we consider necessary to note that the legal status of migrant workers in the Republic of Kazakhstan wasn’t exposed to a complex theoretical and practical research. In this article we aimed to reveal some the theorist – application-oriented questions that arose in the sphere of labor migration, and also to render attempt in business assistance of elimination of those legal collisions which appeared owing to ratification of the international agreements by the Republic of Kazakhstan and to set their ratio with the national legislation. Research objective is studying of a legal status of workers – migrants, generalization and the analysis of separate aspects of their legal status, identification of legislative ways of regulation of work of workers – migrants, and also influence of their activity on improvement of institute of social partnership. Key words: labor law, work, labor migration, worker, employer, internal migration, external migration.